1998
DOI: 10.1590/s0100-879x1998000100005
|View full text |Cite
|
Sign up to set email alerts
|

Aging and immunoglobulin isotype patterns in oral tolerance

Abstract: In the present review we address oral tolerance as an important biological phenomenon and discuss how it is affected by aging. Other factors such as frequency of feeding and previous digestion of the antigen also seem to influence the establishment of oral tolerance. We also analyze immunoglobulin isotypes of specific antibodies formed by tolerant and immunized animals of different ages submitted to different conditions of oral antigen administration. Isotypic patterns were studied as a parameter for assessing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 69 publications
1
18
0
Order By: Relevance
“…In mice, some reports suggest that, with ageing, the levels of total and specific serum IgG and IgM increase (Koga et al, 2000), while other authors found a reduction in specific IgG and IgM in aged animals (Faria et al, 1998). Speziali et al (2009), have recently shown that basal levels of total serum immunoglobulins, IgG and IgA were increased while antigen-specific immunoglobulins, IgG and IgA were reduced in aged mice compared to young ones.…”
Section: B Lymphocytesmentioning
confidence: 99%
“…In mice, some reports suggest that, with ageing, the levels of total and specific serum IgG and IgM increase (Koga et al, 2000), while other authors found a reduction in specific IgG and IgM in aged animals (Faria et al, 1998). Speziali et al (2009), have recently shown that basal levels of total serum immunoglobulins, IgG and IgA were increased while antigen-specific immunoglobulins, IgG and IgA were reduced in aged mice compared to young ones.…”
Section: B Lymphocytesmentioning
confidence: 99%
“…Levels of parasitespecific immunoglobulin G1 (IgG1) and IgG2a were measured by ELISA as described elsewhere (8). A titration curve was plotted to determine the best protein concentration and antibody dilution.…”
mentioning
confidence: 99%
“…circulating antibody formation [37][38][39][40][41][42][43]. Natural feeding of mice has been shown to result preferentially in oral tolerance to dietary components, specially with proteins repeatedly ingested on several consecutive occasions [38,41,44].…”
Section: Different Outcomes Of Mucosal Antigenic Exposuresmentioning
confidence: 99%